A copper site is required for iron transport by the periplasmic proteins P19 and FetP. Issue 10 (11th August 2020) - Chan, Anson C. K.; Lin, Helen; Koch, Doreen; Grass, Gregor; Nies, Dietrich H.; Murphy, Michael E. P.
Abstract : An atypical five-coordinate copper site linked to an adjacent iron site is required for iron-dependent bacterial growth. Abstract : Campylobacter jejuni is a leading cause of food-borne gastrointestinal disease in humans and uropathogenic Escherichia coli is a leading cause of urinary tract infections. Both human pathogens harbour a homologous iron uptake system (termed cjFetM-P19 in C. jejuni and ecFetM-FetP in E. coli ). Although these systems are important for growth under iron limitation, the mechanisms by which these systems function during iron transport remain undefined. The copper ions bound to P19 and FetP, the homologous periplasmic proteins, are coordinated in an uncommon penta-dentate manner involving a Met-Glu-His3 motif and exhibit positional plasticity. Here we demonstrate the function of the Met and Glu residues in modulating copper binding and controlling copper positioning through site-directed variants, binding assays, and crystal structures. Growth of C. jejuni strains with these p19 variants is impaired under iron limited conditions as compared to the wild-type strain. Additionally, an acidic residue-rich secondary site is required for binding iron and function in vivo . Finally, western blot analyses demonstrate direct and specific interactions between periplasmic P19 and FetP with the large periplasmic domain of their respective inner membrane transporters cjFetM and ecFetM.